Peran Google Maps dalam Strategi Promosi dan Penjualan UMKM - Miralda Salsyabillah; Anggi Pranata; Ratu May Yasmin; Misrah Misrah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the transformation of promotional strategies among Micro, Small, and Medium Enterprises (MSMEs) in Suka Makmur Village after utilizing Google Maps as a digital marketing platform. The research focuses on identifying changes in promotional approaches, MSME owners’ perceptions of the effectiveness of Google Maps, and its impact on business visibility and sales performance. The study employed a participatory approach through the Community Service Program (KKN), consisting of several stages, including surveys, socialization, training, and direct mentoring. The research subjects comprised three MSMEs: Seblak Prasmanan, Warung Kopi, and Rumah Jajan By Nisa. The findings indicate that, prior to the intervention, promotional activities were predominantly traditional and limited in reach. After adopting Google Maps, the businesses became more easily discoverable, received positive reviews, and successfully reached customers beyond the local area. This study concludes that the effective use of Google Maps enhances the digital identity of MSMEs, broadens market reach, strengthens competitiveness, and contributes to the local economic growth of Suka Makmur Village.